Analisis Pengendalian Kualitas Produk Bakso Ikan Tuna pada PD. Anugrah Menggunakan Metode Statistical Process Control (SPC) - Nazwa Alya Izabella; Muhammad Naufal Fajar Siddiq; Dipta Fathin Abiyu; Gelbina Setianisa; Eci Mahera; Kharisma Fitri Hapsari (Journal of Innovative and Creativity, 2025)
Quality control is an important aspect in ensuring consistent product quality in the food processing industry, as consistency is a key requirement for maintaining consumer trust. Every food processing company, including PD. Anugrah, is required to minimize quality issues in its products and reduce wasteful activities that do not provide added value. PD. Anugrah is a company engaged in the production of fish-based meatballs made from tuna. In its production process, several types of defects are found, such as inconsistent size, color defects, texture defects, leaking packaging, and insufficient filling. This research aims to analyze waste in the production process and identify the most dominant product defects in order to formulate effective corrective actions. The analytical methods used include the Lean Manufacturing and Statistical Process Control approaches, employing eight key tools in Lean Manufacturingtransportation, inventory, motion, waiting, overproduction, overprocessing, defects, and safety/health injuries and three tools from the Seven Tools of Quality: check sheet, Pareto diagram, and fishbone diagram as instruments to determine the root causes of problems. Based on the results of the Pareto diagram analysis, the main problems reached 87.58%, with the four highest defect factors being inappropriate product size at 24.31%, texture defects at 22.87%, leaking packaging at 20.40%, and color defects at 20.0%. Analysis using the Fishbone Diagram showed that the causes of these defects included human factors, work methods, machinery, materials, environmental conditions, and measurement systems. To reduce the defect rate, improvements are needed in workforce management, machine technology, standardization of methods and measurement, as well as environmental condition management.